Social media for Indonesian and Philippines students - Nurfalah, Farida; Brajadenta, Gara; Siraj, Nurudin; Santika, Rifka Noviani; Forrer, Christine (Universitas Padjadjaran, 2023)
Background: The digital era has changed the behavior of students who are very responsive to technology, especially social media. However, social media has a different role and impact on their life. Purpose: This study aims to find out the interest of Indonesian and Philippines students in using social media, to find out their activities and their opinions about their social media usage. Method: This study used qualitative descriptive with purposive sampling resulting in eight people as informants spread across Indonesia and the Philippines. Results: This study found that almost all students use and have social media accounts. They use it to access education, and entertainment and to increase their local, national, and international knowledge, especially among those who participate in the Merdeka Learning program, while Philippines students participate in the international lecture program. With the existence of social media, they rarely watch television, radio, and newspaper, although there are some Indonesian informants who still like to read newspapers, there are differences in the interest in using social media by Indonesian and Philippines students. Indonesian students use social media such as Facebook, Instagram, YouTube, and Telegram, Meanwhile, Philippines students use Facebook more when interacting with their campus friends. The students see social media changed the pattern of their daily life, for example, the lack of direct social interaction and the increase of cybercrime, while the positive impact of social media is the ability to do storytelling on social media, making it easier to communicate. Conclusion: Philippines students use Facebook more than popular social media such as Instagram and Tiktok, in contrast to Indonesian students who primarily use Instagram and Tiktok. Implication: That both Filipino and Indonesian students utilize social media, but there are differences in their preferences and usage pattern.